A particulate blood analogue based on artificial viscoelastic blood plasma and RBC-like microparticles at a concentration matching the human haematocrit. Issue 39 (23rd September 2022) - Rubio, A.; López, M.; Rodrigues, T.; Campo-Deaño, L.; Vega, E. J.
Abstract : A novel blood analogue fluid able to reproduce the rheological and some physiological characteristics of real human blood at body temperature. Abstract : There has been enormous interest in the production of fluids with rheological properties similar to those of real blood over the last few years. Application fields range from biomicrofluidics (microscale) to forensic science (macroscale). The inclusion of flexible microparticles in blood analogue fluids has been demonstrated to be essential in order to reproduce the behaviour of blood flow in these fields. Here, we describe a protocol to produce a whole human blood analogue composed of a proposed plasma analogue and flexible spherical microparticles that mimic the key structural attributes of RBCs (size and mechanical properties), at a concentration matching the human haematocrit (∼42% by volume). Polydimethylsiloxane (PDMS) flexible microparticles were used to mimic RBCs, whose capability to deform is tunable by means of the mixing ratio of the PDMS precursor. Their flow through glass micronozzles allowed us to find the appropriate mixing ratio of PDMS to have approximately the same Young's modulus ( E ) as that exhibited by real RBCs. Shear and extensional rheology and microrheology techniques were used to match the properties exhibited by human plasma and whole blood at body temperature (37 °C). Finally, we study the flow of our proposed fluid through a microfluidic channel, showing the in vitro reproduction of the multiphase flow effects taking place in the human microcirculatory system, such as the cell-free layer (CFL) and the Fåhræus–Lindqvist effect. A macroscale application in the field of forensic science is also presented, concerning the impact of our blood analogue droplets on a solid surface for bloodstain pattern analysis.